THE EFFECT OF A MIXTURE OF EXTRACTS OF PEGANUM HARMALA SEEDS AND ARTEMISIA HERBA-ALBA LEAVES ON ENTAMOEBA HISTOLYTICA IN VITRO. - Al-Shanawi, Fawzia (Iraqi Journal of Science, 2024)
Entamoeba histolytica was isolated from bloody mucoid stools of patients with amebic dysentery and cultivated on Lock-egg medium to which human serum was added. The parasites were maintained in culture for two weeks during which separate subcultures were prepared.The effect of a water extract and of an alcoholic extract of seeds of Peganum harmala and leaves of Artemisia herba-alba on the viability of E. histolytica was tested. The effect of a combination of the water extracts and of the alcoholic extracts of both plants on amebic viability was also tested at concentrations of 1000 mg / ml and at 1500 mg / ml for two hours. The results showed a marked effect of both combinations of water extracts and of alcoholic extracts on viability of E. histolytica in vitro. The effect was greater at the higher concentration. The highest killing effect was obtained when the extract concentration was 1500 mg / ml , reaching 98.5 % for the alcoholic extracts and 89 % for the water extract. The anti-amebic effect may be due to the high content of alkaloids and saponoids in Peganum seeds complemented by the volatile oils and phenols in Artemisia leaves.